Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1042/bj3610443
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the synaptic protein PICK1 (protein interacting with C kinase 1) with the non-voltage gated sodium channels BNC1 (brain Na+ channel 1) and ASIC (acid-sensing ion channel)

Abstract: Neuronal members of the degenerin\epithelial Na + channel (DEG\ENaC) family of cation channels include the mammalian brain Na + channel 1 (BNC1), acid-sensing ion channel (ASIC) and dorsal-root acid-sensing ion channel (DRASIC). Their response to acidic pH, their sequence similarity to nematode proteins involved in mechanotransduction and their modulation by neuropeptides suggest that they may function as receptors for a number of different stimuli. Using the yeast two-hybrid assay, we found that the PDZ domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…However, whether ASIC1a and ASIC2a are distributed in the growth cones of immature neurons during development is not known. In addition, whether ASIC1a and ASIC2a are presynaptically localized in mature neurons is controversial (Hruska-Hageman et al, 2002;Alvarez de la Rosa et al, 2003;Zha et al, 2006). In this study, we demonstrated that the ASIC1a and ASIC2a subunits are present in axonal growth cones from 3 days in vitro (DIV3) to DIV6 hippocampal neurons.…”
Section: Introductionmentioning
confidence: 73%
“…However, whether ASIC1a and ASIC2a are distributed in the growth cones of immature neurons during development is not known. In addition, whether ASIC1a and ASIC2a are presynaptically localized in mature neurons is controversial (Hruska-Hageman et al, 2002;Alvarez de la Rosa et al, 2003;Zha et al, 2006). In this study, we demonstrated that the ASIC1a and ASIC2a subunits are present in axonal growth cones from 3 days in vitro (DIV3) to DIV6 hippocampal neurons.…”
Section: Introductionmentioning
confidence: 73%
“…In addition to interacting with GluR2, PICK1 interacts specifically with the C-termini of ASIC1 and ASIC2 in central neurons via its PDZ domain [23,24]. ASIC1 is expressed predominantly in small-diameter DRG neurons, whereas ASIC2 is localized to the plasma membrane of small-, medium-, and large-diameter cells of the DRG [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…That conclusion is consistent with previous studies in brain slices and cultured neurons that localized ASIC1 and ASIC2 at dendritic spines Zha et al 2006Zha et al , 2009). In addition, ASIC1 and ASIC2 were enriched in synaptosomal membrane preparations Zha et al 2009) and associated with postsynaptic scaffolding proteins (Duggan et al 2002;Hruska-Hageman et al 2002;Xu & Xiong 2007;Zha et al 2009). Thus, the data suggest that ASIC1 and ASIC2 sit in the postsynaptic membrane.…”
Section: Asic Channels Influence Behavior In Response To Intense Avementioning
confidence: 99%